Answer:
6x² - 10x + 11
Step-by-step explanation:
Step 1: Write expression
(9x² - 6x) + (5 - 4x) + (6 - 3x²)
Step 2: Combine like terms
6x² - 10x + 11
-19/25 if you simply it by 4
Answer:
D. Minimum at (3, 7)
Step-by-step explanation:
We can add and subtract the square of half the x-coefficient:
y = x^2 -6x +(-6/2)^2 +16 -(-6/2)^2
y = (x -3)^2 +7 . . . . . simplify to vertex form
Comparing this to the vertex for for vertex (h, k) ...
y = (x -h)^2 +k
We find the vertex to be ...
(3, 7) . . . . vertex
The coefficient of x^2 is positive (+1), so the parabola opens upward and the vertex is a minimum.
Answer:
The left side
−
2.875
is not greater than the right side
−
2.875
, which means that the given statement is false.
False
Step-by-step explanation:
Using: A^2+b^2=c^2
A&b= (√10)^2=10
10+10=c^2
20=c^2
(take the square root of 20)
c=2√5
Your answer is D